(untitled) (Sebha University Conference Proceedings, 2024)
This study dealt with the phenomenon of heresy, which is considered one of the important and precise matters in Islamic law, and its danger lies in changing the religion and distorting its image by changing and distorting the law. This studying will focus on certain aspects of it, studying the concept of heresy in terms of language and terminology, and mentioning the sayings of scholars in terms of their differences. And their agreement on it, the controls by which innovation is controlled and the distinction between it and sin were mentioned, and knowing when innovation occurs, it is in customs and transactions. Next comes an explanation of the most important reasons that lead to the emergence of these heresies. It has also been explained how to deal with Islamic societies from the spread of heresies and eliminating them.